Career outcomes and satisfaction among graduates of a 4‐year oral health and welfare baccalaureate program at Niigata University, Japan: A cross‐sectional study. - Ishiguro‐Matsumoto, Asuka; Stegaroiu, Roxana; Suwama, Kana; Shibata, Satoko; Yoshihara, Akihiro; Ohuchi, Akitsugu (International Journal of Dental Hygiene, 2023)
Objective: Globally, baccalaureate programs in dental hygiene are increasingly established. In addition, in Japan, many dental hygienists (DHs) and social workers (SWs) are prematurely leaving the workforce. This study aimed to investigate the most recent employment, career outcomes, reasons for a job change, and satisfaction with the job and undergraduate curriculum among graduates of the baccalaureate program at the Department of Oral Health and Welfare (DOHW), Faculty of Dentistry, Niigata University. Methods: All 262 graduates (graduating classes 1–10) of the DOHW were invited to participate in this survey; an original self‐administered questionnaire was distributed to those who consented. Responses were received from 114 (43.5%) graduates. Results: Almost all respondents (89.5%) had dual licensure as both DH and certified SW. They were employed immediately after graduation (99.1%) and at the time of the survey (96.5%). Over 60% of them worked as DHs, mainly in hospitals. SWs mainly worked in administration. Among the 113 respondents who were employed, 39.8% changed jobs at least once. The main reasons for job selection were 'interest in job content' and 'flexible working hours'. Nearly 90% of the respondents felt satisfied or fairly satisfied with their job and their undergraduate education. Conclusions: A quality 4‐year baccalaureate degree program in dental hygiene and social welfare positively influenced graduates' work continuity. Most graduates felt satisfied or fairly satisfied with their job and the undergraduate curriculum. Employment rates within each profession and the prevalence of hospital and administrative roles were higher than national averages. Long‐term studies of graduates' career outcomes are warranted.